Financial literacy as moderation between overconfidence, loss aversion, fear of missing out, and investment decision - Putri Kumalasari; Maretha Ika Prajawati (Jurnal Fokus Manajemen Bisnis, 2025)
In recent years, a surge of young investor in Indoensia has been observed, many of whom rely on peer influence, and limited financial knowledge to make investment decisions. However, this enthusiasm is often not accompanied by adequate financial literacy, making young investors more susceptible to pshychological biases such as overconfidence, loss aversion and fear of missing out. This study examines how overconfidence, loss aversion, and fear of missing out  on the investment decisions of generation Z in Malang City, Indonesia with financial literacy assessed as a moderating variable. In light of the increasing involvement of young investors in Indonesia, this study emphasizes the psychological factors influencing investment behavior. Data were collected through a survey of 96 stock investors, using quantitative methods with purposive sampling, with SPSS version 26 as the statistical tool for data analysis, and with moderated regression analysis used for analysis. The results indicate that although fear of missing out does not have a positive impact on investment decisions, excessive confidence and loss aversion do have a positive impact on investment decisions. The results also show that financial literacy cannot moderate overconfidence, loss aversion, and fear of missing out. This study is interesting because it examines how behavioral biases, financial literacy, and investing behavior interact with Indonesia's generation Z using the theory of planned behavior  paradigm. By integrating behavioral finance concepts with emotional considerations, the study offers novel insights into young investors' decision processes. Nevertheless, the findings are constrained to generation Z investors in Malang City, Indonesia, limiting the generalizability to broader populations.